Adobe Dreamweaver CS4. - Adobe Creative Team (San Jose, Calif. : AdobePress ; Berkeley, Calif. : Peachpit, 2009)
Adobe Dreamweaver CS4 Classroom in a Book is the fastest, easiest, most comprehensive way to learn Adobe Dreamweaver CS4. Features 11 lessons covering how to create and manage web sites, build rich interactive interfaces, incorporate graphics, text, and video, and use Photoshop Smart Objects.
Keywords: Dreamweaver (Computer file); Web sites -- Authoring programs; Web sites -- Design